A protocol for the implementation of new technology in a highly complex hospital environment: the operating room. (3rd March 2020) - Misser, Navin Sewberath; Jaspers, Joris; Zaane, Bas Van; Gooszen, Hein; Versendaal, Johan
Medical equipment is implemented in highly complex hospital environments, such as operating rooms, in hospitals around the world. In operating rooms (ORs), technological equipment is used for surgical activities and activities in support of surgeries. The implementation of government policies in hospitals has resulted in varying implementation activities for (medical) equipment. These result in varying lead times and success rates. An integral and holistic protocol for implementation does not yet exist. In this study, we introduce a protocol for the implementation of (medical) equipment in ORs that consists of implementation factors and implementation activities. Factors and activities are based on data from a systematic literature review and an explorative survey among surgical support staff on factors for the successful implementation of technological and (medical) equipment in ORs. The protocol consists of five factors and related implementation activities: the establishment of a project plan, organisational preparation, technological preparation, maintenance, and training.